2005
DOI: 10.1080/13561820500082974
|View full text |Cite
|
Sign up to set email alerts
|

Factors in implementing interprofessional education and collaborative practice initiatives: Findings from key informant interviews

Abstract: Health Canada (the federal government department in Canada responsible for health issues) commissioned a research team to conduct an environmental scan and research report in order to understand interprofessional education and collaborative patient-centred practice (IECPCP). This paper presents the findings from semi-structured telephone interviews with key informants conducted as part of the environmental scan. Grounded theory analysis was employed in order to identify factors associated with interprofessiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 4 publications
2
61
0
5
Order By: Relevance
“…Residents and senior clinicians in other studies have also identified their domain as medical knowledge, while downplaying the importance of IP team-based care skills. 10,23 However, this study is the first to the author's knowledge to explore resident perceptions of IP team-based care within their continuity clinics and to show that IP team function is not the sole determinant of the educational impact of IP teamwork.…”
Section: Discussionmentioning
confidence: 99%
“…Residents and senior clinicians in other studies have also identified their domain as medical knowledge, while downplaying the importance of IP team-based care skills. 10,23 However, this study is the first to the author's knowledge to explore resident perceptions of IP team-based care within their continuity clinics and to show that IP team function is not the sole determinant of the educational impact of IP teamwork.…”
Section: Discussionmentioning
confidence: 99%
“…The American Council on Pharmaceutical Education [30], the Pew Health Professions Committee [31], the United States Institute of Medicine [13], and the University of Minnesota [32] had begun work on defining and delineating interprofessional competencies for healthcare planning and delivery. In Canada, Health Canada [10], the Canadian Interprofessional Health Collaborative [CIHC] [7], HealthForceOntario [11], Barker and Oandasan [8], and Barker, Bosco, and Oandasan [9] described the need for interprofessional competencies and provided strategies to move toward improved interprofessional care.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Worldwide, healthcare services could be improved by providing interprofessional, collaborative, patient-centred care that improves patient outcomes while reducing healthcare costs [7][8][9][10][11][12][13][14]. Yet, despite the diverse and extensive literature on change management and human resources management, few empirically based models provide the breadth and depth necessary to deal with the complexities of transforming current healthcare systems into care planning and delivery systems that are interprofessional, evidence-based, and cost-effective.…”
Section: Introductionmentioning
confidence: 99%
“…The local IPE Champion can be defined as the leader and ambassador for both the strategic and operational aspects of the curriculum with management and research responsibilities (Barker et al 2005;Oandasan & Reeves 2005). Their major task is to maintain strong partnerships across professions, organisations and institutions (Bjørke & Haavie 2006;Gilbert 2005).…”
Section: Insert Table 141 Herementioning
confidence: 99%